The Relationship Between Profit and Export Performance Revisited: Evidence from Turkish Companies - Esmeray, Azize; Esmeray, Murat (International Journal of Economics and Financial Issues, 2016)
In this study, the linkage between export and profit performance is analyzed. In order to see the relation, we employ Least Square analysis for the period of 1993-2014 by taking 500 largest companies in Turkey. It is concluded that both export and profit performance have positive effect on each other’s. On the other hand, export positive effect is more powerful than profit effect on export. Keywords: Profit, Export, 500 Largest Companies. JEL Classifications: F4, F14